PKM Kewirausahaan Pizza Rolls Varian Topping - Hikmayani Subur; Abdul Rajab; Ratna S; Sri Utami; Wahyu Muh. Syata (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Pizza rolls are snacks in the form of small rolls that usually contain typical pizza ingredients, such as tomato sauce, cheese, meat such as pepperoni or sausage, and various other toppings. The outer crust of pizza rolls is usually made from thin dough such as bread or pastry, then fried or baked until crispy. Pizza rolls are a small snack that combines the classic taste of pizza with a practical form that is easy to eat at any time. Its popularity makes it a favorite choice for casual events, parties or just an afternoon snack. Seeing the increasing food trend, the author took the initiative to make pizza rolls with topping variants in order to provide education to people who want to become entrepreneurs in the culinary field, especially snacks. Pizza rolls are known as a practical and delicious snack, but their health benefits depend on the ingredients used and how they are made. Some of the potential benefits of pizza rolls, especially if made with quality ingredients and consumed in moderation, are a source of fast energy, rich in protein, a source of calcium, contain vitamins and minerals, a healthy alternative with modifications, and improve mood. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained were (1) The participants responded well to the training in making pizza rolls with topping variants; (2) Strong motivation and interest from training participants so that it supports the transfer of information and skills from service providers to participants, and each participant can fully absorb the training material offered; and (3) The training product for making pizza rolls with topping variants can be consumed daily and can be used as an entrepreneurial product.